Evaluation of [68Ga]Ga-DOTA-TCTP-1 for the Detection of Metalloproteinase 2/9 Expression in Mouse Atherosclerotic Plaques - Kiugel M; Hellberg S; Käkelä M; Liljenbäck H; Saanijoki T; Li XG; Tuomela J; Knuuti J; Saraste A; Roivainen A (MDPI AG, 2022)
Background: The expression of matrix metalloproteinases 2/9 (MMP-2/9) has been implicated in arterial remodeling and inflammation in atherosclerosis. We evaluated a gallium-68 labeled peptide for the detection of MMP-2/9 in atherosclerotic mouse aorta.
Methods: We studied sixteen low-density lipoprotein receptor deficient mice (LDLR-/-ApoB100/100) kept on a Western-type diet. Distribution of intravenously-injected MMP-2/9-targeting peptide, [68Ga]Ga-DOTA-TCTP-1, was studied by combined positron emission tomography (PET) and contrast-enhanced computed tomography (CT). At 60 min post-injection, aortas were cut into cryosections for autoradiography analysis of tracer uptake, histology, and immunohistochemistry. Zymography was used to assess MMP-2/9 activation and pre-treatment with MMP-2/9 inhibitor to assess the specificity of tracer uptake. Results: Tracer uptake was not visible by in vivo PET/CT in the atherosclerotic aorta, but ex vivo autoradiography revealed 1.8 ± 0.34 times higher tracer uptake in atherosclerotic plaques than in normal vessel wall (p = 0.0029). Tracer uptake in plaques correlated strongly with the quantity of Mac-3-positive macrophages (R = 0.91, p < 0.001), but weakly with MMP-9 staining (R = 0.40, p = 0.099). Zymography showed MMP-2 activation in the aorta, and pre-treatment with MMP-2/9 inhibitor decreased tracer uptake by 55% (p = 0.0020).
Conclusions: The MMP-2/9-targeting [68Ga]Ga-DOTA-TCTP-1 shows specific uptake in inflamed atherosclerotic lesions; however, a low target-to-background ratio precluded in vivo vascular imaging. Our results suggest, that the affinity of gelatinase imaging probes should be steered towards activated MMP-2, to reduce the interference of circulating enzymes on the target visualization in vivo. -